Design of Fishing Vessel of Catamaran Type In Waterways of East Kalimantan (40 GT). Issue 1 (January 2021) - Alamsyah,; Setiawan, W; Dwi Cahya, E; Ika Wulandari, A; Suardi,; Alifantio, A
Abstract: Fishing vessel craftsmen in the East Kalimantan area have made several changes to the design of fishing vessels to get more catch. Changes were made to the main dimension which resulted in changes in ship characteristics such as speed and stability of the ship. This purpose of research to determine the main dimensions and stability analysis of catamaran hull fishing vessels. The method used is the parent ship method and optimization using maxsurf software. The results obtained were as follows: LOA = 16.2 [m], B = 6 [m], B1 = 1 [m], T = 1 [m], H = 2 [m], Cb = 0.192, Vs = 6.5 [knots], and number of crew = 5 person. The required of Catamaran is a power of 134, 498 [HP] consist of two engine 70 [HP]. Based on the results of critical analysis stability on catamarans, the maximum GZ value occurs at a heeling of 20ᴼ. The maximum GZ value in loadcase 1 is 2.326 [m], loadcase 2 is 2.15 [m], and loadcase 3 is 2.18 [m]. The GM values for all loadcase scenarios are not less than 0.15 [meters]. All of them accepted the IMO and HSC 2000 Annex 7 Multihull criteria.